2016
DOI: 10.1016/j.idc.2015.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Candidiasis

Abstract: Invasive candidiasis is a collective term that refers to a group of infectious syndromes caused by a variety of species of Candida, 5 of which cause most cases. Candidemia is the most commonly recognized syndrome associated with invasive candidiasis. Certain conditions may influence the likelihood for one species versus another in a specific clinical scenario, and this can have important implications for selection of antifungal therapy and the duration of treatment. Molecular diagnostic technology plays an eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
223
3
12

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(239 citation statements)
references
References 148 publications
1
223
3
12
Order By: Relevance
“…It is responsible for 72.3% of all fungal infectious agents, followed by Candida krusei and Candida glabrata, Candida tropicalis and Candida parapsilosis. Moreover, other studies have also reported that Candida species were dominant pathogens [10]. However, in Taiwan and Korea, the most prevalent pathogens were Cryptococcus and Aspergillus, respectively [7,11].…”
Section: Discussionmentioning
confidence: 90%
“…It is responsible for 72.3% of all fungal infectious agents, followed by Candida krusei and Candida glabrata, Candida tropicalis and Candida parapsilosis. Moreover, other studies have also reported that Candida species were dominant pathogens [10]. However, in Taiwan and Korea, the most prevalent pathogens were Cryptococcus and Aspergillus, respectively [7,11].…”
Section: Discussionmentioning
confidence: 90%
“…Candidemia now ranks as the third most common cause of health care-associated bloodstream infections (BSI) and is the leading cause of BSIs in intensive care units (ICUs) (3). Nevertheless, treatment of candidiasis, from superficial to invasive infections, still relies on a limited drug arsenal composed mainly of amphotericin B, triazoles (mostly fluconazole), and echinocandins (13).…”
Section: Resultsmentioning
confidence: 99%
“…was indicated as one of the main etiological agents of BSIs, responsible for 7.6% of the cases 2 . Among the most common causes of BSIs is candidemia, which is the syndrome most frequently associated with invasive candidiasis 5 and high mortality rates (40% to 60%) 2 . Invasive candidiasis is one of the major clinical manifestations of the Candida genus caused by C. albicans and non-albicans 6 Candida, these, in turn, respond to at least 50% of the invasive infections by Candida spp.…”
mentioning
confidence: 99%